Vitamin D Status in Children With Short Stature: Accurate Determination of Serum Vitamin D Components Using High-Performance Liquid Chromatography–Tandem Mass Spectrometry - Xu, Bei; Feng, Yue; Gan, Lingling; Zhang, Yamei; Jiang, Wenqiang; Feng, Jiafu; Yu, Lin (Frontiers in Endocrinology, 2021)
Objective: Vitamin D is critical for calcium and bone metabolism. Vitamin D insufficiency may negatively affect skeletal mineralization and bone growth rate during childhood, thus affecting height and health. Vitamin D status in children with short stature is sparsely reported. The purpose of the current study was determine various vitamin D components by high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) to better explore vitamin D storage of short stature children in vivo. Methods: Serum circulating levels of 25-hydroxyvitamin D2 [25(OH)D2], 25-hydroxyvitamin D3 [25(OH)D3] and 3-epi-25-hydroxyvitamin D3 [3-epi-25(OH)D3, C3-epi] were accurately computed. Total 25(OH)D [t-25(OH)D], and ratios of 25(OH)D2/25(OH)D3 and C3-epi/25(OH)D3 were respectively calculated. Free 25(OH)D [f-25(OH)D] was also measured. Results: 25(OH)D3 and f-25(OH)D levels in short stature subgroups 2 (school age: 7~12 years old) and 3 (adolescence: 13~18 years old) were significantly lower compared with those of healthy controls, whilst C3-epi levels and C3-epi/25(OH)D3 ratios in all the three short stature subgroups were significantly higher than the corresponding healthy cases. Based on cut-off values developed by Endocrine Society Recommendation (but not suitable for methods 2 and 3), sufficient storage capacities of vitamin D in short stature subgroup 1, 2 and 3 were 42.8%, 23.8%, and 9.0% as determined by Method 3 [25(OH)D2/3+25(OH)D3], which were lower compared with those of 57.1%, 28.6%, and 18.2% as determined by Method 1 [25(OH)D2+25(OH)D3+C3-epi] and 45.7%, 28.5%, and 13.6% as determined by Method 2 [25(OH)D2/3+25(OH)D3+C3-epi]. 25(OH)D2 levels were found to be weakly negatively correlated with 25(OH)D3, and higher 25(OH)D3 levels were positively correlated with higher levels of C3-epi in both short stature and healthy control cohorts. Furthermore, levels of f-25(OH)D were positively associated with those of 25(OH)D3 and C3-epi in children. Conclusions: Current LC-MS/MS technique separated 25(OH)D2 from 25(OH)D3, and distinguished C3-epi from 25(OH)D3 isomer. Just detecting t-25(OH)D [25(OH)D2+25(OH)D3] overestimated vitamin D storage in children, and short stature patients had more severe vitamin D deficiency compared with healthy subjects. Ratios of C3-epi/25(OH)D3 and 25(OH)D2/25(OH)D3 might be alternative markers for vitamin D catabolism/storage in short stature children. Further studies are needed to explore relationships and physiological roles of various vitamin D metabolites.